Freshwater gastropods diversity hotspots: Three new species from the Uruguay River (South America) - Gutiérrez Gregoric, Diego Eduardo (2016)
Background: The Atlantic Forest is globally one of the priority ecoregions for biodiversity conservation. In Argentina, it is represented by the Paranense Forest, which covers a vast area of Misiones Province between the Paraná and Uruguay rivers. The Uruguay River is a global hotspot of freshwater gastropod diversity, here mainly represented by Tateidae (genus Potamolithus) and to a lesser extent Chilinidae. The family Chilinidae (Gastropoda, Hygrophila) includes 21 species currently recorded in Argentina, and three species in the Uruguay River. The species of Chilinidae occur in quite different types of habitats, but generally in clean oxygenated water recording variable temperature ranges. Highly oxygenated freshwater environments (waterfalls and rapids) are the most vulnerable continental environments. We provide here novel information on three new species of Chilinidae from environments containing waterfalls and rapids in the Uruguay River malacological province of Argentina. Materials and Methods: The specimens were collected in 2010. We analyzed shell, radula, and nervous and reproductive systems, and determined the molecular genetics. The genetic distance was calculated for two mitochondrial markers (cytochrome c oxidase subunit I-COI- and cytochrome b -Cyt b-) for these three new species and the species recorded from the Misionerean, Uruguay River and Lower Paraná-Río de la Plata malacological provinces. In addition, the COI data were analyzed phylogenetically by the neighbor-joining and Bayesian inference techniques. Results: The species described here are different in terms of shell, radula and nervous and reproductive systems, mostly based on the sculpture of the penis sheath. Phylogenetic analyses grouped the three new species with those present in the Lower Paraná-Río de la Plata and Uruguay River malacological provinces. Discussion: Phylogenetic analyses confirm the separation between the Uruguay River and the Misionerean malacological provinces in northeast Argentina. These new endemic species from the Uruguay River add further support to the suggestion that this river is a diversity hotspot of freshwater gastropods (with 54 species present in this basin, 15 of them endemic). These endemic species from environments with rapids and waterfalls should be taken into account by government agencies before the construction of dams that modify those ecologic niches in the Uruguay River.